Green Mussel Shells (Perna Viridis) To Reduce the pH Of Liquid Waste Resulting from Tofu Processing - Nanang Ruhyat; Syukur Pribadi (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2022)
The food processing industry in every production process always produces waste. One of the food industries in the Jakarta area is the tofu making industry. Waste from the tofu processing process is divided into 2 types, liquid waste and solid waste. Problems that arise include the occurrence of deposition and decomposition of organic matter in water bodies which causes silting of rivers, and causes unpleasant odors. An alternative solution to reduce the pollution load is to use filter media with material from green mussel shells (Perna viridis). Meanwhile, green scallop shells are solid waste for the environment which were used in this study as a filter medium for the liquid waste left over from tofu processing and tested in the home-scale tofu processing industry in the Semanan area, West Jakarta. The test results on the pH level of the waste, green mussel shells have been able to reduce the degree of acidity by up to 52%. Visually, turbidity and foam in the liquid waste from tofu processing are reduced. It is undeniable that filter media from green mussel shells can be used as an alternative filter material for liquid waste. This research has succeeded in reducing the impact of liquid waste pollution from tofu processing